Fingerprint Matching Based on Two- Dimensional Discrete Hartley Transform - Rdwan, Roqia Khaled; Amer, Mohammed Mahmoud (Journal of natural sciences, life and applied sciences, 2019)
The main aim of this research is to study fingerprint matching based on the discrete two-dimensional Hartley transformation and its comparison with the discrete two-dimensional Wavelet transformation and the Gabor filter. In this research،a methodology based on extracting standard deviation and energy characteristics based on two-dimensional discrete time Hartley Transform for fingerprint matching was proposed according to an approved database of the University of Bologna and the FVC2002 database، The results obtained were compared with discrete wavelet transform (DWT) and experimental results showed that the methodology proposed using Hartley transform reduces the FAR from 21.48% to 16.74% according to the University of Bologna database and also from 31.29% to 28.69% according to FVC2002 database.
Keywords: Hartley transform; discrete wavelet transform; Gabor filter; feature extraction; fingerprint matching